Rap1 in the VMH regulates glucose homeostasis - Kaneko, Kentaro; Lin, Hsiao-Yun; Fu, Yukiko; Saha, Pradip K.; De la Puente-Gomez, Ana B.; Xu, Yong; Ohinata, Kousaku; Chen, Peter; Morozov, Alexei; Fukuda, Makoto (JCI insight, 2021)
The hypothalamus is a critical regulator of glucose metabolism and is capable of correcting diabetes conditions independently of an effect on energy balance. The small GTPase Rap1 in the forebrain is implicated in high-fat diet-induced (HFD-induced) obesity and glucose imbalance. Here, we report that increasing Rap1 activity selectively in the medial hypothalamus elevated blood glucose without increasing the body weight of HFD-fed mice. In contrast, decreasing hypothalamic Rap1 activity protected mice from diet-induced hyperglycemia but did not prevent weight gain. The remarkable glycemic effect of Rap1 was reproduced when Rap1 was specifically deleted in steroidogenic factor-1-positive (SF-1-positive) neurons in the ventromedial hypothalamic nucleus (VMH) known to regulate glucose metabolism. While having no effect on body weight regardless of sex, diet, and age, Rap1 deficiency in the VMH SF1 neurons markedly lowered blood glucose and insulin levels, improved glucose and insulin tolerance, and protected mice against HFD-induced neural leptin resistance and peripheral insulin resistance at the cellular and whole-body levels. Last, acute pharmacological inhibition of brain exchange protein directly activated by cAMP 2, a direct activator of Rap1, corrected glucose imbalance in obese mouse models. Our findings uncover the primary role of VMH Rap1 in glycemic control and implicate Rap1 signaling as a potential target for therapeutic intervention in diabetes.